Resolute Character in Jack Reacher’s Killing Floor: Analysis of Politeness and Impoliteness Strategies - Fikri, Maulana Muhammad; Bahruddin, Uril; Al Anshory, Abdul Muntaqim (Jurnal Bahasa dan Sastra, 2025)
This study investigates how politeness and impoliteness strategies in Killing Floor by Lee Child are used to navigate power dynamics, reflect Jack Reacher’s moral reasoning, and shape his character development. Drawing on Brown and Levinson’s politeness theory, Leech’s maxims, and Culpeper’s impoliteness strategies, the study explores how Reacher’s language functions as a tool for asserting authority, building trust, and resolving conflict. A qualitative descriptive approach was employed, with data collected through close reading and document analysis of the novel. Dialogue excerpts involving Reacher were selected based on their relevance to politeness and impoliteness strategies. Each excerpt was manually coded, categorized by strategy, and organized thematically to reveal patterns across different narrative contexts. Data analysis followed Miles and Huberman’s (1994) model, involving data reduction, display, and conclusion drawing, to ensure systematic and credible interpretation. The findings identify three key patterns: (1) Reacher’s use of impoliteness to resist authority and challenge power structures; (2) his selective use of politeness to build trust and alliances; and (3) his tactical manipulation of language for survival and control. This study fills a critical gap in pragmatic literature by offering a unified analysis of politeness and impoliteness, showing how these strategies jointly contribute to narrative progression and character transformation. Beyond literary analysis, it highlights how strategic language reflects moral decision-making and power negotiation, offering insights for pragmatics education and communication in high-stakes interactions.